«Ad ogni modo però il repubblicano deve essere istrutto»: A first Analysis of the Educational Reform of the Republic of Brescia (Italian Review of Legal History, 2019)
This paper offers a first analysis of the scholastic reform adopted by the republican government of Brescia (March 1797 - November 1797) with a comparative glance at the revolutionary French school system and to the “normal” method adopted by the Austrian government of Lombardy. The comparative analysis of the different types of reforms developed in the two different areas allows to define the cultural attitudes of the élites of Brescia as well as their political ambitions. In fact, is remarkable that the Educational committee of the government highlights in the project the connection of democracy and education, using a rhetoric attitude close to the French one: education is considered as the root of democracy and the unique solid ground for the survival of a republican government. On the contrary, at a pedagogic level, the project of the young Republic follows the reforms adopted by the Austrian Government in Lombardy and accept the so-called “normal method” of Abbas Felbiger. This pedagogical model is based on the regulation and control of the students during the lessons and in the organization of the scholar system seeks to spread only useful notions in the lower classes and not to allow a cultural elevation that could break the perpetuation of the social hierarchy.Even if the Repubblica Bresciana represents a really brief experience in the history of this territory - it was added to the Repubblica Cisalpina in a few months - the educational reform marks a point in the evolution of the scholastic system and its effects will be noticeable for the following decades. Is difficult to say if the choice of the “normal method” actually reflects a sincere conviction of the superiority of the Austrian model or if it represents a first way to reach the uniformity of the scholar system within Lombardy in order to make easier a unification in fieri. In any case this operation shows the wide range of possibilities and of knowledge of the political élite of this Republic and highlights how difficult is to accept the definition of “Jacobin triennum” in order to define the political life of the years 1796-1799 in northern Italy.
Keywords: Republic of Brescia; Education; Austrian enlightened absolutism; Jacobin Triennium; French Revolution